Relevansi Teori Kritis Mazhab Frankfurt dalam Pembentukan Kebijakan Publik yang Demokratis dan Emansipatif di Bidang Perdagangan di Indonesia - Raymundus Anthony Samadi (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This paper analyzes the relevance of the Frankfurt School’s Critical Theory in shaping public policy in Indonesia’s trade sector, particularly in the context of implementing Law Number 7 of 2014 on Trade. Using key concepts of Critical Theory—such as alienation, reification, instrumental rationality, and emancipation—this study evaluates how the structure of modern political economy can generate social inequality, the marginalization of small business actors, and the dominance of market-driven logic in national trade practices. A thematic analysis approach based on a literature review is employed to examine relevant scholarly works, including theories from Adorno, Horkheimer, Habermas, and contemporary critical theorists. The findings indicate that trade policies tend to be technocratic, efficiency-oriented, and insufficiently reflective of economic democracy, social justice, and empowerment principles for grassroots economic actors as mandated by the constitution. Such conditions reproduce structural injustices, particularly for MSMEs, which are often marginalized within a competitive trade system dominated by large capital. Therefore, more inclusive, participatory policy designs that are sensitive to structural inequalities are urgently needed. This study concludes that Critical Theory serves as a robust conceptual framework for analyzing power relations within the trade sector while also offering a transformative direction for policy development. Strengthening deliberative public spheres, enhancing MSME protection, and transforming power relations are essential steps toward achieving trade policies that are fairer, more humanistic, and emancipatory.